2013
DOI: 10.1093/ndt/gft312
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab for minimal change disease in adults: long-term follow-up

Abstract: Our study reinforces the role of rituximab as a GC-sparing agent in the challenging GC-dependent and multirelapsing MCD patients. In this emerging therapeutic field randomized studies with extended follow-up will add important information regarding optimal treatment, relapse and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 24 publications
5
55
0
Order By: Relevance
“…The beneficial effect of rituximab was confirmed in two recent studies (26,27). Bruchfeld et al reported the longterm follow-up of 16 patients (9 women, 7 men; aged 19-73 years) with frequent-relapsing, steroid-dependent (prednisone 5 and 20 mg/d), or steroid-resistant MCD treated with rituximab (26).…”
Section: Discussion Of Casementioning
confidence: 88%
See 2 more Smart Citations
“…The beneficial effect of rituximab was confirmed in two recent studies (26,27). Bruchfeld et al reported the longterm follow-up of 16 patients (9 women, 7 men; aged 19-73 years) with frequent-relapsing, steroid-dependent (prednisone 5 and 20 mg/d), or steroid-resistant MCD treated with rituximab (26).…”
Section: Discussion Of Casementioning
confidence: 88%
“…Bruchfeld et al reported the longterm follow-up of 16 patients (9 women, 7 men; aged 19-73 years) with frequent-relapsing, steroid-dependent (prednisone 5 and 20 mg/d), or steroid-resistant MCD treated with rituximab (26). Patients had experienced 3 to .20 relapses despite previous immunosuppressive therapy, including cyclophosphamide, calcineurin inhibitors, azathioprine, MMF, chlorambucil, and/or levamisole.…”
Section: Discussion Of Casementioning
confidence: 99%
See 1 more Smart Citation
“…Notably, only 8 out of 25 patients had nephrotic range proteinuria at baseline. In their retrospective analysis, Bruchfeld et al [12] observed good efficacy after RTX therapy with achievement of remission in 15 out of 16 MCD patients. In addition, the majority of patients remained relapse-free during a follow-up period of at least 12 months.…”
Section: Efficacy Of Rtx In Adult MCD and Fsgsmentioning
confidence: 99%
“…A prospective study from Japan revealed mild infusion reactions such as cough and hiccough, and an exanthema as predominant complications, whereas 1 patient developed mild leukopenia related to RTX during follow-up [11]. Bruchfeld et al [12 ]reported 2 patients suffering from transient hypotension and 1 patient with itchy and red eyes. In their prospective study, Ruggenenti et al [3] observed no immediate side effects, whereas infectious complications such as gastroenteritis, varicella or flu-like syndrome, and noninfectious complications like seizures or melanoma in situ were reported.…”
Section: Adverse Event Spectrum Of Rtx Treatmentmentioning
confidence: 99%